Character Education Transformation through Science Technology Society (STM) Approach Towards Golden Indonesia 2045 - Nurfajri, M.; Wahab, Wahab (Jurnal Pengabdian Nusantara, 2024)
The transformation of education in Indonesia towards the vision of Golden Indonesia 2045 is crucial in the context of character education, science, and technology within society. This transformation aims to shift the education system from being overly permissive without clear control to one that balances freedom and responsibility, guided by wise oversight. Technological advancements have reshaped learning methods in the digital era, making them more interactive and collaborative. Character education plays a vital role in shaping the nation's identity, emphasizing ethical values that should be taught from an early age through both formal and informal institutions. The Science, Technology, and Society (STS) approach integrates scientific knowledge with social issues, helping students connect learning with real-life situations. The vision of Golden Indonesia 2045 requires the younger generation to be not only intellectually intelligent but also emotionally and spiritually grounded, creating well-rounded and wise individuals. Thus, education is expected to shape a generation capable of facing global challenges and becoming the key to the nation's success in the future.